Pengaruh Literasi Keuangan dan Fear of Missing Out (FoMO) terhadap Gaya Hidup Konsumtif - Muhamad Radit; Indra Andriyana; M. Azka Irawan; Sri Mulyeni (International Forum of Researchers and Lecturers, 2026)
The massive penetration of social media and e-commerce has fundamentally transformed the shopping habits of society, particularly among university students and Generation Z. Relentless promotional bombardments, coupled with the accessibility of